ORGANIZATIONAL AND ECONOMIC SUPPORT FOR THE MANAGEMENT OF THE DEVELOPMENT OF HUMAN CAPITAL IN THE DIGITAL ECONOMY (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This article explores the exchange of information based on innovative technologies, based on its dissemination, and its theoretical description, a structure that allows relationships between many companies.
Keywords: innovative system, innovative companies, innovative development strategy, digital competencies, systemic approach, digital infrastructure.